Analysis Of Supply And Demand For Seginim Rice In Bengkulu City (Case Study At The Panorama Traditional Market In Bengkulu City) - Muhammad Evriandes Andes; Herri Fariadi; Rika Dwi Yulihartika (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: To determine the supply chain flow of Seginim rice in the Panorama Traditional Market in Bengkulu City and the factors influencing demand for it. Methodology: The research method uses a combination of qualitative and quantitative descriptive techniques, including questionnaires and interviews. The sample of traders comprised six shops/traders, and the sample of consumers comprised 86 individuals, selected using the accidental sampling technique. Data analysis was carried out using descriptive and quantitative methods, as well as multiple linear regression analysis. Results: The results showed that the supply chain for Seginim rice in the traditional market in Panorama, Bengkulu City, starts with the producers (namely farmers), then moves to wholesalers, agents or collectors, and finally to retailers (Panorama Market), before being distributed to consumers. The factors affecting demand for Seginim rice in the Panorama traditional market in Bengkulu City are consumer tastes and income, while the number of family dependants and the prices of Seginim and IR64 rice have no effect.Findings: It is evident that demand for Seginim rice in the Panorama market is high, with almost every rice stall selling Seginim rice. Conclusion: Rice supplied to the traditional Panorama market in Bengkulu comes from wholesalers who buy directly from rice farmers in the Seginim area. Type of paper: Research Paper